Emissions from southeastern U.S. Grasslands and pine savannas: Comparison of aerial and ground field measurements with laboratory burns. (June 2015) - Aurell, Johanna; Gullett, Brian K.; Tabor, Dennis
Abstract: Emissions from prescribed burns of a managed longleaf pine ( Pinus palustris ) forest and grass/savanna fields in western Florida were measured by simultaneous aerial and ground sampling. Results were compared with measurements made in an open burn laboratory test facility using biomass gathered from the same stands. Measurements included polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), particulate matter (PM2.5 ), elemental carbon (EC), organic carbon (OC), black carbon (BC), brown carbon (BrC), polychlorinated dibenzo-p-dioxins (PCDDs), and polychlorinated dibenzofurans (PCDFs). The flaming phase (high modified combustion efficiency) was characterized by high levels of BC and BrC yet low levels of VOCs. In general, ground-based measurements of PM2.5, BC, and BrC reported marginally higher emission factors than those measured in the plume by aerostat (balloon)-lofted instruments. The optically-determined BC emission factor was approximately ten times higher than many previously reported results. Simultaneous BC and EC measurements showed that EC values were, on average, 42% lower than the BC values, lending uncertainty to the common use of EC measurements as a BC surrogate. PAH emission factors were indistinguishable across the sampling scenarios, while PCDDs/PCDFs saw a significant decline in the laboratory testing. Limited distinctions in particle-related emissions between aerial and ground measurements suggest sampling bias between these methods. Emission factor distinctions between laboratory burn simulations and field tests appear primarily related to lower combustion efficiencies in the latter, perhaps due to higher biomass moisture or surface wetness. Graphical abstract: Highlights: PM2.5, BC, BrC emission factors were marginally higher from ground vs air samples. BC and BrC emission factors increased with modified combustion efficiency. EC emission factors were over 40% lower than BC values. Laboratory testing showed lower PCDD/PCDF emission factors than field testing.